DEVELOPMENT OF STUDENTS’ PERSONAL POTENTIAL DURING IMPLEMENTATION OF ENVIRONMENTAL PROJECTS - Tolochko, Svitlana (Theoretical and Methodical Problems of Children and Youth Education, 2024)
The article substantiates peculiarities of the development of students’ personal potential during the implementation of environmental projects, and describes definitions of the concepts “personal potential”, “project activity”, “educational project” and “prescribing roles”. The purpose is to substantiate the impact of the level of development of students’ personal potential on the quality of their environmental projects. The objectives of the study are: to analyze the state of development of the problem of developing students’ personal potential during the implementation of environmental projects; to clarify the essence and structure of the concepts “personal potential”, “project activity”, “educational project”, “prescribing roles”; to reveal peculiarities of influence of the level of development of students’ personal potential on quality of their environmental projects. To achieve this goal and certain tasks, the following methods were applied: theoretical: theoretical analysis and generalization of literary sources; comparison, classification, and generalization to clarify the content of basic concepts of the study; system method, idealization; empirical: pedagogical observation, generalization of pedagogical experience. Based on the analysis of studies of the concept of “personal potential”, we interpret this term as a set of individual resources: knowledge, skills, value orientations, abilities, and motivational attitudes that allow a person to function effectively in society and achieve success in various spheres of life, personal and professional goals, show moral and ethical values as the basis of responsible behavior and citizenship, represent critical thinking and creativity, ensure the psychological well-being of youth. Basic concepts and methods of ecological education are allocated, which include concepts of ecological education, methods of ecological education, and value of ecological education. Important aspects of project technologies are emphasized: active learning, development of critical thinking, teamwork, independence and responsibility, and integration of knowledge. The role of analyzing skills and knowledge of each member of the group, assigning roles of a project manager, environmental expert, engineer, financial analyst, organizer, marketer, etc., are updated. It is summed up that taking into account the personal potential of each member of the group of senior students to carry out environmentally oriented project activities through prescribing their roles is an important aspect for successfully overcoming the environmental consequences of war in a particular region.